The emergence of perovskite solar cells - Green, M; Ho-Baillie, A; Snaith, H (2014)
The past two years have seen the unprecedentedly rapid emergence of a new class of solar cell based on mixed organic-inorganic halide perovskites. Although the first efficient solid-state perovskite cells were reported only in mid-2012, extremely rapid progress was made during 2013 with energy conversion efficiencies reaching a confirmed 16.2% at the end of the year. This increased to a confirmed efficiency of 17.9% in early 2014, with unconfirmed values as high as 19.3% claimed. Moreover, a broad range of different fabrication approaches and device concepts is represented among the highest performing devices-this diversity suggests that performance is still far from fully optimized. This Review briefly outlines notable achievements to date, describes the unique attributes of these perovskites leading to their rapid emergence and discusses challenges facing the successful development and commercialization of perovskite solar cells. © 2014 Macmillan Publishers Limited.